YAŞLILARA YÖNELİK SOSYAL POLİTİKALAR: AKTİF YAŞLANMA YAKLAŞIMININ COVID-19 PANDEMİSİ EKSENİNDE DEĞERLENDİRİLMESİ - Teke, Dilay; Yenihan, Doç. Dr. Bora (Fırat University, 2022)
Demografik dönüşümler dünyada yaşlanan bir nüfusun ön plana çıktığını göstermektedir. Yaşlanan nüfus karşısında “aktif yaşlanma yaklaşımı” bir çözüm olarak sunulmaktadır. Bu yaklaşım Birleşmiş Milletler (BM), Dünya Sağlık Örgütü (WHO), Avrupa Birliği (AB) tarafından da önemle ele alınmakta ve çeşitli endekslerle toplumların aktif, sağlıklı, üretken yaşlanma düzeyleri tespit edilmektedir. Aktif yaşlanma yaklaşımı beşeri sermayeye yatırım, yaşlı refahını arttırmaya dair politika olarak değerlendirilmektedir. Yaklaşımın sağlık, katılım, güvenlik başlıklarıyla yaşlı bireylerin yaşam kalitelerinin iyileştirilmesi amaçlanmaktadır. Ancak Covid-19 pandemisi ile yaşlıların sağlıklarını korumak amacıyla çeşitli kısıtlamalar uygulanmıştır. Aktif yaşlanma yaklaşımı açısından pandemi sürecindeki bu önlemler başarılı ve sağlıklı yaşlanmayı etkilemiştir ve yaşlıların yeni ihtiyaçları gündeme gelmiştir. Ayrıca pandemi sürecinde yaşlılar içerisinde farklı dezavantajlara sahip bireylerin de olduğu anlaşılmıştır. Bu bağlamda çalışmanın amacı pandemi sürecinde risk grubunda olan yaşlılar için aktif yaşlanma yaklaşımının geliştirilmesi gerektiğini ortaya koymaktır. Farklı dezavantajların kesiştiği yaşlılar için kapsamlı politikaya duyulan ihtiyacı açıklamaktır. Çalışma aktif yaşlanma yaklaşımını konu almakta ve pandemi döneminde yaşlıların belirginleşen ihtiyaçları için aktif yaşlanma yaklaşımının düzenlenmesi gerektiğine vurgu yapmaktadır. Çalışmanın yönteminde aktif yaşlanmaya dair ulusal ve uluslararası literatür ile belgeler taranmıştır. Covid-19 pandemisi ile ilgili veriler, bültenler ve gazete haberleri incelenmiştir. Yaşlanan nüfus istatistiksel bilgilerle açıklanmıştır. Covid-19 pandemisi sürecinde risk grubunda olan yaşlılar için sunulan hizmetler aktif yaşlanma yaklaşımı çerçevesinde analiz edilmiştir. Yaşlılar için geliştirilen sosyal politikaların önemi vurgulanmıştır. Aktif yaşlanma yaklaşımının gelecekte de önemle üzerinde durulacağı ifade edilmiştir. Sonuç olarak bu değerlendirmeler kapsamında pandemi sürecinde aktif yaşlanma yaklaşımının güncellenmesi gereği ön plana çıkmıştır. Yaşlılara yönelik farklı sosyal politikalarla birlikte aktif yaşlanma yaklaşımının eşgüdüm içerisinde uygulanması önerilmiştir. Ulaşılabilir hedeflerle aktif yaşlanma yaklaşımının daha net ve uygulanabilir olacağı ifade edilmiştir.

Demographic transformations show that an aging population has come to the fore in the world. In the face of the aging population, the “active aging approach” is presented as a solution. This approach is also taken seriously by the United Nations (UN), World Health Organization (WHO), European Union (EU), and active, healthy and productive aging levels of societies are determined using with various indices. The active aging approach is considered as a policy to invest in human capital and increase the welfare of the elderly. The approach aims to improve the quality of life of the elderly with the headings of health, participation and safety. However, with the Covid-19 pandemic, various restrictions have been applied to protect the health of the elderly.Regarding the active aging approach, the precausions in pandemic process have affected successful and healthy aging, and the new needs of the elderly have come to the fore. In addition, it has been understood that there are individuals with different disadvantages among the elderly during the pandemic process. In this context, the aim of the study is to reveal that an active aging approach should be developed for the elderly who are in the risk group during the pandemic process. It is to explain the need for comprehensive policy for the elderly at the intersection of different disadvantages. The study focuses on the active aging approach and emphasizes that the active aging approach should be regulated for the emerging needs of the elderly during the pandemic period. In the method of the study, national and international literature and documents on active aging were scanned. Data, bulletins and newspaper news about the Covid-19 pandemic were examined. The aging population is explained by statistical information. The services provided for the elderly who are in the risk group during the Covid-19 pandemic process were analyzed within the framework of the active aging approach. The importance of social policies developed for the elderly was emphasized. It has been stated that the active aging approach will also be emphasized in the future. As a result, within the scope of these evaluations, the need to update the active aging approach in the pandemic process has come to the fore. It has been suggested that the active aging approach be implemented in coordination with different social policies for the elderly. It has been stated that the active aging approach will be more clear and applicable with achievable targets.
Social Policies For The Elderly: Evaluation Of Active Aging Approach On The Axis Of The Covid-19 Pandemic